Code-switching from french into english as a reflection of personalization function in Netflix series “Emily in Paris” - Vladimirovna, Tutova Ekaterina (2022)
The plot of the series “Emily in Paris” is rather simple. It also should be noted that most of the people “Emily” meets are able to converse in English, but find it hard to find equivalents in English for their speech. We should cite first as an example the word “la plouc”, which is used as a reference to Emily’s New York style and manners. It can be translated as “country girl”. “Bonjour, la plouc!” The second French word, which follows Emily is “ringarde”, common in English. A French designer, who sees a fluffy accessory attached to the bag, calls Emily “common”. It is recommended that further research of Code-switching (CS) in series language will be made to examine speaker’s intentions in a larger sample of inclusions, as well as their syntactic structure, semantics, and psychological motivation.